Rancang Bangun Alat Memilih Minuman Dengan Perintah Suara Berbasis Arduino - Fitri Haryono; Paryanta Paryanta (Sekolah Tinggi Manajemen Informatika dan Komputer AUB - Indonesia, 2017)
Vending machine is a man- made technology which is used as a container of drinking water. The purpose of the making of this machine is to give flexibility for people to place and take drinking water by using a dispenser or a box as a display for various drinking water products in Indonesia. However, the operation of the dispenser is still done manually. This will decrease the effectivity of the machine and even if there is a human error or machinary malfunction, the water from the tap will overflow. Consequently, it will increase the water waste. If this problem continues to happen, it will decrease the effectivity and efficiency values of this machine. The main objective of the research is to design and make voice order activated vending machine with Arduino Uno basis. It is expected that the machine will be able to help human to use the automatic vending machine ia a more effective way. This research employs descriptive method. As a whole the machine will be divided into blocks of structures, they are input, process unit, and output. Input consists of voice censor, movemnet censor, and distance censor which are used as automatic order giver to the process unit so that the order can be received well by the process unit and can be forwarded to the output block. The structure which serves as process uit is Arduino Uno R3. The output block is a Modul ISDI700 which produces voice and motor dc that pumps drinking water. This voice order vending machine is expected to give more advantages and easiness for people.The expected result is the machine could measure the capacity of the glass automatically so that it will not overflow the glass.From the research, it can be concluded that this machine has voice activated censors to choose kinds of drink, PIR censor as a human detector, and ultrasonic censor to control the capacity and the location of the glass. The control can be set automatically and controlled by Arduini Uno.Key Words: automatic, Voice Censor, Arduino Uno R3